2023
DOI: 10.5530/pj.2023.15.65
|View full text |Cite
|
Sign up to set email alerts
|

Development of Patient Safety Management Learning Model Based on Problem Based Learning Integrated Soft Skill Higher Level Thinking for Health Students in Samarinda

Abstract: Background: Nursing students who participate in clinical practice in hospitals are not ready to provide quality care in maximizing patient safety. This study aims to develop a Problem Based Learning Patient Safety (PBLPS) conceptual model design that stimulates high-level thinking soft skills for students and finds PBLPS learning tools. Method: Research and Development (R&D), which is a research method that aims to produce new products through a development process. The stages of the research method consist of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…Furthermore, we argue that creativity and innovation benefit from experimentation and creative play with new ideas and ways of working, characterized by the concept of an experimentation-supportive climate. This can be seen as an important precursor to group improvisation, which resembles the state of temporary group creativity 33,34 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we argue that creativity and innovation benefit from experimentation and creative play with new ideas and ways of working, characterized by the concept of an experimentation-supportive climate. This can be seen as an important precursor to group improvisation, which resembles the state of temporary group creativity 33,34 .…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with research (Tuharea, 2022) with a value of Exp(B)=17.274, which shows that families with poor economic status have a 17 times greater risk of toddlers becoming stunted compared to families with sufficient economic status. A good family economic status makes it easier for parents to obtain health services, learning or meeting other needs for their toddlers, (Hilda et al, 2023;Parellangi et al, 2023, Ernyasih et al, 2023 Research (Sutriyawan et al, 2020) also shows a value of Exp(B)=2.065, which means that basic socio-economic levels have a 2 times greater risk of experiencing stunting. These results are in line with research (Rufaida et al, 2020) which shows that low family income provides a 2,344 times risk for toddlers experiencing stunting.…”
Section: Relationship Between Parental Income and Incidence Of Stuntingmentioning
confidence: 99%
“…Antibacterial tests using durian seeds carried out by Sumitha et al, 2018 31 found that they contain secondary metabolites such as flavonoids, tannins and polyphenols which can kill pathogenic bacteria in drinking water such as Stapylococcus aureus, Escherichia coli, so they can be used in the water treatment sector, pharmaceuticals, and nanotechnology. 57…”
Section: Durian Seedsmentioning
confidence: 99%